Micro CT Analysis of Hard Tissue Debris Accumulation Created by SAF vs. ProTaper systems - Diyar Kh Bakr; Hussien Al-Hwaizi; Raid Salman (Erbil Dental Journal)
Background and objectives: Hard tissue debris is deposited routinely during root canal system instrumentation. A new instrument had been marketed with the aim of optimum shaping of all parts of the canal system, however, no information present about the amount of debris removal compared to conventional rotary system. This study investigated the amount of debris accumulated when the canal instrumented by SAF compared with ProTaper by using high resolution computed tomography (micro CT).